The Influence of Location and Satisfaction on Customer Loyalty at BRI Link Pinang Lombang Atas Labuhan Batu Utara - Hansyah, Praida; Nurliza, Nadia; Nasution, Era Fazira; Naibaho, Innatul Jamroh; Ruslyani, Zichan (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2024)
This study aims to analyze the influence of Location and Satisfaction on Customer Loyalty at BRI Link Pinang Lombang Atas, Labuhan Batu Utara. The research employed a quantitative approach using questionnaires distributed to 55 respondents. Data were analyzed using SPSS through validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that Location has a positive but not significant effect on Customer Loyalty. In contrast, Satisfaction has a positive and significant effect on Customer Loyalty. Simultaneously, Location and Satisfaction significantly influence Customer Loyalty with a coefficient of determination (R²) of 0.962. This implies that 96.2% of the variation in Customer Loyalty can be explained by Location and Satisfaction, while the remaining 3.8% is influenced by other factors outside this study. These findings highlight that customer Satisfaction is the dominant factor in shaping Loyalty, whereas Location serves as a supporting factor.